Who are they, where do they come from? Reasons to be a teacher in Nicaragua (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This article describes the findings generated in the Systematization carried out between 2019 and 2020 with students, who participated in the Process of Selection of candidates for Teacher Training in Normal Schools, convened by the Ministry of Education MINED and which was accompanied in the framework of the articulation of educational subsystems, by the National Autonomous University of Nicaragua, UNAN Managua, through the Vice President for Student Affairs VAE. The systematization exercise recovers reflections and experiences from the voice of its protagonists that allow documenting important lessons to strengthen Initial Teacher Training. In this case we focus and share one of the dimensions addressed in this task; the characterization and motivational factors of the student who applies to enter as a Normalist and graduate as a Teacher of Primary Education. Being Educational Quality a central objective and a challenge to move to paths of prosperity, opportunity and human development, the study rescues in the narrative of its actors, keys for reflection and joint action of the meaning that the income of a generation of Normalists with a vocation to effectively and positively impact quality education for girls and boys in our country.
Keywords: Initial Teacher Training; Educational Quality; Human Development; Motivation; Teacher Training